De cuerpos-territorio y disidentificaciones lesboeróticas. Las encrucijadas subjetivas en la narrativa de Yolanda Arroyo Pizarro (Dossier: Producir presente: tocar el cuerpo, escritura, mujeres, paisajes, afectos. Narrativa contemporánea de escritoras en América Latina) - Falconí Trávez, Diego Fernando (2018)
This article intends to, from the vertex between gender studies and post/decolonial theories, examine key elements regarding the narrative of Puerto Rican author Yolanda Arroyo Pizarro which allow understanding the construction of subjectivities through various writings in which race, class, coloniality and sexual desire are constantly tensed; to the extent that, sometimes, they articulate political-aesthetic projects that seem contradictory and that serve to understand certain contemporary identity crossroads. In line with this hypothesis, this essay analyzes both the anti-racist as well as the queer perspective of the author, trying to understand her complex enunciation and the various impositions and resistances of certain women in the Caribbean.